The toxicity of neem (Azadirachta indica), citronella (Cymbopogon nardus), castor (Ricinus communis), and clove (Syzygium aromaticum) oil against Spodoptera frugiferda - Danar Dono; Yusup Hidayat; Tarkus Suganda; Syarif Hidayat; Neneng Sri Widayani (CROPSAVER, 2020)
An important pest in corn plantation recently reported in Indonesia was Spodoptera frugiperda, a polyphagous pest that have a fast spread rate and caused high damage on young corn. One control that able to use is botanical insecticide. This experiment aims to determine the toxicity of neem, jatropha, clove, and citronella oil (concentrations of 0.1% and 0.05%) against S. frugiferda in corn. Tests carried out using the feeding assay or residue on corn leaves (size 5 x 5 cm). Then, the leaf treatment was given to 10 larvae of S. frugiferda (instars 2) for 48 hours. After that, the feed replaced with untreated feed. The test results showed that concentration neem oil of 0.1% caused the highest mortality of S. frugiferda. Neem oil exposure is also able to inhibit the time of larval development, reduce the percentage of feed consumption, and the weight of pupa the S. frugiferda. Other vegetable oils exposure gave lower mortality in the test insects and some treatments were not significantly different from the controls on the parameters of larval development, pupae weight, and percentage of feed consumption. Neem oils showed strong toxicity against S. frugiperda larvae with  Lethal Concentration 50 (LC50) of 0.079 % (CI (95%) 0.066 – 0.095%) and LC95 of 0.338% (CI (95%) 0.024-0.567%).